KAJIAN ASPEK SPASIAL PENYAKIT BERCAK UNGU (A lternaria porri Cif. (Ell) PADA TANAMAN BAWANG MERAH - Nirwanto, Herry (MAPETA, 2008)
The research was conducted at ex-rice field farm in countryside of Klerek, district of Junrejo, Batu. The research took place in rainy season from October until December 2005. Research location resided at height 800 m above sea level. To understand the distribution of purple blotch disease at each observation time, data was obtained from the amount of leaf infection at every crop clump of sample from each experiment plot. The result of the research showed that at age 49 and 52 days after planting, patogen distributed randomly. At the time of early observation 49 days after planting, the distribution of disease followed theory distribution, that is, poisson distribution (p== 0,57). Hereinafter, at age 52 and 55 days, pathogen disseminate aggregately, by increasing age until age 61 days after planting, the distribution of patogen reverse to have random character. The development of disease in the early observation was linear and at age 58-61 days after planting,  it started in fonn of curvilinier. Key words: Alternaria porri, bawang merah, distribusi, laju infeksi